Effect of microstructure on the adhesion strength of TiBx coating on Ti6Al4V substrate. Issue 4 (15th February 2021) - Wu, Bi; Gao, Siyang; Xue, Weihai; Li, Shu; Duan, Deli
Abstract: TiB x coatings were deposited on Ti6Al4V and Si (100) wafer substrates by D.C. magnetron sputtering with various target-to-substrate distances (T.S. distances) from 50 mm to 200 mm. The influence of T.S. distance on the microstructure, hardness and adhesion strength of TiB x coatings and Ti6Al4V substrate system was investigated. Results showed that the microstructure of TiB x coatings transformed from dense to fibre columnar grain with the increase in T.S. distance, whilst the hardness decreased from 20.9 GPa to 9.4 GPa. The Rockwell-C indentation adhesion strength grade was also improved from HF6 to HF1. An adhesion evaluation factor G, which is related to the mechanical properties and the microstructure of TiB x coating, is proposed based on the test results. The adhesion strength increased with G, which corresponded well with the results of indentation test. The high-speed rubbing test with a sliding speed of 300 m/s was performed to check the Al-adhesion resistance of the TiB x coating against Al–hBN seal coating.